An exploration of what Grade 7 Natural Science teachers know, believe and say about biodiversity and the teaching of biodiversity - Isaacs, Dorelle (Rhodes University, Faculty of Education, Department of Education, 2016)
In the context of the newly implemented Curriculum and Assessment Policy Statements (CAPS) for Natural Science, this study explores what Grade 7 Natural Science teachers know, believe and say about biodiversity and the teaching of biodiversity. Despite its significance to environmental sustainability, biodiversity loss is accelerating in South Africa and internationally, driven by unsustainable economic development models, population growth and associated problems of habitat loss and widespread pollution. Against the backdrop of these challenges, this study shares insights into how teachers' biodiversity knowledge relates to the CAPS and to international agreements and policies on biodiversity. The study seeks to inform teacher education and support programmes and future curriculum implementation decisions, especially those associated with the Fundisa for Change programme. The study is designed as a qualitative case study inquiry that has used classroom observation, semistructured interviews and document (textbook) analysis to generate data. Theories of teacher cognition (after Shulman, 1987) were used to gain an understanding of teachers' biodiversity knowledge. Different environmental and biodiversity metaphors and narratives were reviewed to gain an understanding of how teachers represented biodiversity and Kronlid & Ã–hman's work on environmental ethics (2012) provided a framework for considering teachers' values and ethical responses to biodiversity. The study found that the biodiversity knowledge of the teachers in these three case studies was mostly limited to what they access in the curriculum and textbooks. Secondly, there appears to be the assumption that if teachers teach from certain textbooks, they will meet the Specific Aims for Natural Science, as well as implement the process skills which are the 'new' knowledge according to the Senior Education Specialist. It was found that teachers' close adherence to activities prescribed in the textbook seems to limit the depth, scope and criticality of their biodiversity teaching. The study also revealed that all three teachers expressed a pragmatic view of the value of biodiversity. The study recommends that the Natural Science CAPS as well as textbook authors should reflect a more systemic approach to biodiversity knowledge, recognising the interrelations and interdependence of the ecological systems that make up biodiversity "“ including relationships with humans "“ and convey a sense of the changeability of biodiversity. Natural Science teachers should be supported in broadening their understanding of biodiversity and biodiversity loss. They should be encouraged and supported to develop or adapt textbook material where necessary and develop learner activities that will encourage their learners to question, deliberate, look for cause and effect, and seek solutions. This may help to realise the final recommendation, that learners and teachers become citizen scientists who will access and contribute to the various biodiversity databases and so join scientists in generating biodiversity knowledge.
Keywords: Uncatalogued